2019
DOI: 10.2147/vhrm.s197638
|View full text |Cite
|
Sign up to set email alerts
|

<p>Intracardiac thrombus in a patient with catastrophic antiphospholipid syndrome: an autopsy case report and review of the literature</p>

Abstract: Antiphospholipid syndrome (APS) is an autoantibody-mediated acquired thrombophilia characterized by venous and/or arterial thromboses, pregnancy morbidity (predominantly repeated fetal losses), and the presence of phospholipid antibodies. The estimated annual incidence of APS is 5 new cases per 100,000 people. The most common thrombotic events in patients with APS in order of frequency are stroke, transient ischemic attack, deep vein thrombosis, and pulmonary embolism. Patients with APS may develop an intracar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…On the one hand, it is suggested that antiphospholipid antibodies act under several conditions to promote thrombus formation, such as antibodies having various roles, such as in promoting platelet aggregation, binding to platelet membrane proteins, inhibiting fibrinolysis and anticoagulant activity, promoting inflammation; binding to beta 2 glycoprotein I (β2GPI) expressed on the surface of endothelial cells, and causing the cells to turn into a procoagulant and proinflammatory phenotype. However, all these conditions are not sufficient to promote thrombosis, and a second condition is required, respectively the endothelial lesion that may be the direct result of the SARS-CoV-2 infection [31].…”
Section:  Discussionmentioning
confidence: 99%
“…On the one hand, it is suggested that antiphospholipid antibodies act under several conditions to promote thrombus formation, such as antibodies having various roles, such as in promoting platelet aggregation, binding to platelet membrane proteins, inhibiting fibrinolysis and anticoagulant activity, promoting inflammation; binding to beta 2 glycoprotein I (β2GPI) expressed on the surface of endothelial cells, and causing the cells to turn into a procoagulant and proinflammatory phenotype. However, all these conditions are not sufficient to promote thrombosis, and a second condition is required, respectively the endothelial lesion that may be the direct result of the SARS-CoV-2 infection [31].…”
Section:  Discussionmentioning
confidence: 99%
“…One of these patients was a female teenager who had APS associated with systemic lupus erythematosus. 15 In APS patients with intracardiac thrombosis, adequate maintenance anticoagulation therapy heparin and warfarin (target INR 3.0-4.0) are required. The role of intervention in surgery remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The right atrial chamber was the most frequent location of the intracardiac thrombus; however, thrombus was identified in the left atrium and left ventricle in some cases. One of these patients was a female teenager who had APS associated with systemic lupus erythematosus 15 …”
Section: Discussionmentioning
confidence: 99%
“…Se ha tratado de asociar esta complicación al subtipo del anticuerpo, sin embargo, la evidencia no es concluyente, pues en algunos casos se ha relacionado más con el anticuerpo antibeta 2 glicoproteína I y el anticoagulante lúpico mientras que otros han relacionado los anticuerpos anticardiolipina IgG o IgA, este último en IAM con elevación del ST. Se han reportado casos fatales en pacientes jóvenes, donde las manifestaciones cardiacas ocurren por desórdenes inmunes y por su asociación con fenómenos trombóticos (25)(26)(27)(28)(29)(30).…”
Section: Discussionunclassified